Diversification in a biodiversity hotspot–The evolution of Southeast Asian rhacophorid tree frogs on Borneo (Amphibia: Anura: Rhacophoridae) - Hertwig, Stefan T.; Schweizer, Manuel; Das, I.; Haas, A. (Elsevier Inc, 2013)
The tree-frog family Rhacophoridae is a major group contributing to the high pecies richness and reproductive diversity among vertebrates of Sundaland. Nonetheless, rhacophorid evolution, specially on Borneo, has not been studied within a phylogenetic context. In this study, we examine the phylogenetic relationships of 38 (out of 41) Bornean species of Rhacophoridae, in combination with data from previous phylogenetic studies. In the final super matrix of 91 species, we analyse sequence data from two mitochondrial and three nuclear genes. The resulting trees show the genus Rhacophorus as a paraphyletic assemblage. As a consequence, we transfer Rhacophorus appendiculatus and R. kajau to two other genera and propose the new phylogeny-based combinations- Kurixalus appendiculatus and Feihyla kajau, respectively. Furthermore, we use our phylogenetic hypotheses to reconstruct the evolution of reproductive modes in rhacophorid tree frogs. Direct development to the exclusion of a free larval stage evolved twice independently, once in an ancestor of the Pseudophilautus + Raorchestes clade in India and Sri Lanka, and once within Philautus in Southeast Asia. The deposition of egg clutches covered by a layer of jelly in Feihyla is also present in F. kajau and thus confirms our generic reassignment. The remarkably high diversity of rhacophorid tree frogs on Borneo is the outcome of a complex pattern of repeated vicariance and dispersal events caused by past changes in the climatic and geological history of the Sunda shelf. We identified geographic clades of closely related endemic species within Rhacophorus and Philautus, which result from local island radiations on Borneo